Pattern Formation and Stability in Magnetic Colloids 2020
DOI: 10.5772/intechopen.81123
|View full text |Cite
|
Sign up to set email alerts
|

Convection Flow of MHD Couple Stress Fluid in Vertical Microchannel with Entropy Generation

Abstract: Entropy generation of fully developed steady, viscous, incompressible couple stress fluid in a vertical micro-porous-channel in the presence of horizontal magnetic field is analysed in this work. The governing equations for the flow are derived, and nondimensionalised and the resulting nonlinear ordinary differential equations are solved via a rapidly convergent technique developed by Zhou. The solution of the velocity and temperature profiles are utilised to obtain the flow irreversibility and Bejan number. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Lopez et al (2017) have numerically analysed the entropy generation in nanofluid flow through a vertical microchannel with non-linear radiative heat. Abiodun et al (2018) investigated the steady, fully developed convection flow of MHD couple stress fluid in a vertical micro-porous-channel and discussed the combined effects of fluid wall interaction parameter (FWIP), couple stresses, rarefaction, magnetic parameter and effective temperature ratio on the velocity profile, temperature profile, HFF 30,10 entropy generation and Bejan number. Agboola et al (2018) have analytically investigated entropy generation analysis on a fully developed natural convection flow through a vertical microchannel by considering the Hall effect.…”
Section: Hall Effect Of Natural Convection Flowmentioning
confidence: 99%
“…Lopez et al (2017) have numerically analysed the entropy generation in nanofluid flow through a vertical microchannel with non-linear radiative heat. Abiodun et al (2018) investigated the steady, fully developed convection flow of MHD couple stress fluid in a vertical micro-porous-channel and discussed the combined effects of fluid wall interaction parameter (FWIP), couple stresses, rarefaction, magnetic parameter and effective temperature ratio on the velocity profile, temperature profile, HFF 30,10 entropy generation and Bejan number. Agboola et al (2018) have analytically investigated entropy generation analysis on a fully developed natural convection flow through a vertical microchannel by considering the Hall effect.…”
Section: Hall Effect Of Natural Convection Flowmentioning
confidence: 99%
“…They have noticed that the impact of diffusivity is dominant in a couple stress fluid flow. In a vertical channel, an electrically conducting couple stress fluid flow subjected to the fluid friction irreversibility has been studied by Opanuga et al 14 Including, they have studied the impact of various flow parameters such as effective temperature ratio, rarefaction, and FWI parameter on the fluid motion, thermal field, entropy, and Bejan number in detail through graphs. Many authors have studied the flow and heat transfer analysis in different aspects by using various effects 15–27 …”
Section: Introductionmentioning
confidence: 99%
“…In a uniformly heated microchannel, the entropy generation analysis under the impact of Darcy porous medium has been depicted by Abbassi. 8 The combined effects of various physical parameters such as Prandtl number, Reynolds number, and Brinkmann number in a parallel plate channel subjected to irreversibility analysis have been displayed by Erbay et al 9 In a vertical microchannel, the irreversibility investigation in an electrically conducting couple stress fluid under the effect of magnetism, Joule heating, and viscous dissipation has been discussed by Abiodun et al 10 By utilizing generators of a longitudinal vortex, the entropy generation in a channel has been depicted by Ebrahimi et al 11 Several investigations have been done on irreversibility analysis in a channel with different geometries. [12][13][14][15][16][17][18][19][20] The impact of Hall current on natural convection flow in a microchannel via analyzing irreversibility has been represented by Agboola et al 21 In their study, the impact of WATDR, Hall current, and fluid wall interaction parameter (FWIP) on fluid motion, temperature, irreversibility, and irreversibility ratio has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Including, it is also important from the perspective of industrial applications, such as the refreshing of metallic plates in a shower, extrusion of polymer liquids, and it has increased carrying fluid flow through the thin film 29,30 . Regarding this, the analysis of couple stress fluid between two parallel channels under the effects of magnetism, Joule heating, and the convective boundary has been discussed by Kareem et al 31 The couple stress fluid flow between parallel channels by utilizing Adomin decomposition method has been reported by Adesanya et al 32 In an MHD couple, stress fluid through a vertical microchannel subjected to the analysis of irreversibility has been displayed by Opanuga et al 33 They have observed the different parameters, such as rarefaction, the ratio of effective temperature, and FWIP on fluid motion, thermal field, irreversibility, and irreversibility ratio in detail through graphs. In a similar manner, many researchers have conducted their research on flow and heat transfer analysis in different channels in different aspects of the physical model 34‐41 …”
Section: Introductionmentioning
confidence: 99%